Epidemiology of injuries during the Wheelchair Basketball World Championships 2018: A prospective cohort study - Hollander, K.; Kluge, S.; Glöer, F.; Riepenhof, H.; Zech, A.; Junge, A. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Several international sports federations have implemented a standardized injury reporting system during their championships. However, very few studies have investigated athletes with disabilities during major championships apart from the Paralympic Games. Therefore, the aim of this study was to assess the rate and characteristics of injuries during the Wheelchair Basketball World Championships 2018 (WBWC). This prospective cohort study was conducted during the WBWC held in Hamburg, Germany, from August 16 to August 26, 2018. Physicians or physiotherapists of all 28 participating teams (total 336 players) were asked to report all newly incurred injuries (with location, diagnosis, cause, and estimated duration of absence) daily on a standardized injury report form. Prevalence and incidence rates were calculated. Medical staff of 11 teams (132 players) reported 100 injuries, equivalent to 75.8 per 100 players (95% CI: 60.9-90.7) or 68.9 per 1000 player-days (55.4-82.4). Eight time-loss injuries were reported (6.1 injuries per 100 players [95% CI: 1.9-10.3] or 5.5 injuries per 1000 player-days [1.7-9.3]). More injuries were incurred during matches (n = 68) than during training. Most injuries affected the neck/cervical spine (16%), thoracic spine/upper back (15%), and shoulder (14%). The most frequent diagnosis was muscle spasms (25%), the most frequent cause was overuse (52%). A high rate of non-time-loss injuries compared to Paralympic Games was reported. Future studies should focus on the etiology of muscle spasms and further identify injury mechanisms of traumatic and overuse injuries in wheelchair basketball players to develop adequate preventive measures.